Characteristics of the generative periode of one-year species of Trifolium L. which were introduced in the Ukraine Right-Bank Forest-Steppe - Kryklyva, S.D. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The dynamics of blossom of Trifolium alexandrinum L. and Trifolium apertum Bobr. were studied in conditions of Right-Bank Forest-Steppe of the Ukraine. Morfometric characteristics of inflorescence and infructescence on the shoots of different orders are given. The seed production is calculated.